2017
DOI: 10.1016/j.ijid.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset neonatal sepsis in Arab states in the Gulf region: two-year prospective study

Abstract: LOS poses a major burden in this area, which could be due to the increasing care of premature babies. Gram-negative organisms, particularly Klebsiella spp, are having an increasing role in LOS in this region, with high levels of resistance to third-generation cephalosporins. NICUs in the area should create a platform through which to share experience in reducing neonatal sepsis and contribute to a common antibiotic stewardship program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 38 publications
14
33
1
Order By: Relevance
“…In our study, The case-fatality was 16.8%, which is similar to those reported from Asian countries (16%) [10,20]. E. coli were responsible for about one-third (11/ 34) of deaths due to LOS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, The case-fatality was 16.8%, which is similar to those reported from Asian countries (16%) [10,20]. E. coli were responsible for about one-third (11/ 34) of deaths due to LOS.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have revealed that gram-positive bacteria were the main causative organisms, with CoNS responsible for the most common organism of LOS [18,19]. Majeda et al reported that CoNS alone was responsible for more than one-third of LOS cases in Arab states in the Gulf region [20]. Matthew et al found that for nearly 20 years, CoNS was the organism most responsible for late-onset sepsis in their NICU [21].…”
Section: Discussionmentioning
confidence: 99%
“…The required demographic, clinical and outcome details, and evidence on possible risk factors for infection were identied from previously published studies of LOS. 11-14 Neonatal risk factors data collected included the use of mechanical ventilation and duration, total parenteral nutrition (TPN) use and duration, central line use and duration, gestational age, and birth weight. Maternal risk factors included prolonged rupture of membranes (PROM), chorioamnionitis, intrapartum antibiotic prophylaxis (IAP) use, and use of antenatal steroids.…”
Section: Methodsmentioning
confidence: 99%
“…Lack of proper infection control measures and appropriate guidelines in some ICUs in the Gulf region might have a signicant impact on the increasing incidence of neonatal infections and the outline of causative organisms. 11 In Oman, the incidence, risk factors, and causative organisms of LOS have not been studied comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from some European countries [ 23 ] and Brazil [ 24 ] have documented the contributions of CoNS in neonatal sepsis, which could result in increased risk of mortality and morbidities., There are limited data on the incidence of CoNS in neonatal sepsis in Kuwait [ 25 , 26 ]. However, there are no studies on the molecular characteristics of CoNS associated with neonatal sepsis in Kuwait.…”
Section: Introductionmentioning
confidence: 99%